A Human Rights-Based Approach to Health in Assisted Reproductive Care in Spain - Rocío Paricio-del-Castillo; María de los Ángeles Cano-Linares; Mónica Díaz de Neira Hernando (Journal of Family and Reproductive Health)
Objective: Assisted reproductive techniques (ART) have evolved significantly since the early 20th century, driven by biomedical advances and profound socio-cultural shifts worldwide, particularly in Spain. This expansion has enabled access to parenthood in previously inaccessible situations, such as infertility and diverse family structures, yet it also poses risks of human rights violations. Materials and methods: A reflective analysis is conducted on the practices in Spanish healthcare related to assisted reproduction, based on national legislation and its alignment with international human rights legislation. The review of international standards was carried out using normative sources from the United Nations (UN), the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), the World Health Organization (WHO), the Universal Declaration on Bioethics and Human Rights of UNESCO, and those adopted in the European regional context by the Council of Europe, particularly the Convention on Human Rights and Biomedicine. Results: This article examines potential human rights violations within Spain's ART healthcare framework, identifying gaps in international human rights compliance. Despite Spain's progressive legislation on ART, discrepancies remain with evolving European standards, especially concerning oocyte donation and donor anonymity. Conclusion: The goal is to promote reflection, improve the quality of care, and protect the health and rights of women, children, and families using ART, while ensuring that clinical practices align with human rights principles.